Nickel-Catalyzed Reductive Cross-Coupling of Aryl Halides - Qian, Qun; Zang, Zhenhua; Wang, Shulin; Chen, Yang; Lin, Kunhua; Gong, Hegui (Synlett, 2013)
This work highlights unsymmetrical biaryl compounds via direct nickel-catalyzed reductive coupling of two aryl halides. By tuning the ligand structures, the reaction of two electron-enriched aryl halides also provided the coupling product in good yields, with an excess of 1.4 equivalents of one of the halides. The mild reaction conditions display excellent functional-group tolerance and generally gave the coupling products in moderate to good yields. In addition to aryl bromides, activated aryl chlorides are effective.
Keywords: nickel; cross-coupling; biaryl; aryl halides